AL-KAFA’AH FI AL-NIKAH - Najmah Sayuti (Kafa`ah: Journal of Gender Studies, 2015)
Kafa'ah in marriage is basically equality, suitability and proportionality between the prospective couples getting married. Humans are required to kafa'ah in religion and religiosity. Non-Muslims can't kafa'ah with Muslims because of inequalities in beliefe. Some kafa'ah that should be considered in marriage is nasab, religion, belief or religiosity, profession, liberty and property.